Dye Adsorption Behavior of Graphene Oxide. (2019) - Ranjan, Pranay; Balakrishnan, Jayakumar; Thakur, Ajay D.
Abstract: We demonstrate the use of dispersed graphene oxide (DGO) as dye adsorbents for the degradation of methylene blue (MB) dye. Reduction in absorbance of MB solution in the presence of DGO is studied using optical spectroscopy. A threshold concentration of 0.125 ppm of DGO is found to be required for effective degradation of 1ppm MB solution in water